Classification modeling based on surface porosity for the grading of natural cork stoppers for quality wines - Oliveira, Vanda; Knapic, Sofia; Pereira, Helena (Food and Bioproducts Processing)
Abstract The natural cork stoppers are commercially graded into quality classes according with the homogeneity of the external surface. The underlying criteria for this classification are subjective without quantified criteria and standards defined by cork industry or consumers. Image analysis was applied to premium, good and standard quality classes to characterize the surface of the cork stoppers and stepwise discriminant analysis (SDA) was used to build predictive classification models. The final goal is to analyze the contribution of each porosity feature and propose an algorithm for cork stoppers quality class classification. This study provides the knowledge based on a large sampling to an accurate grading of natural cork stoppers.
Keywords: Classification algorithm; Discriminant analysis; image analysis; natural cork stoppers; Porosity; quality classes

The cork viewed from the inside - Lagorce-Tachon, Aurélie; Karbowiak, Thomas; Loupiac, Camille; Gaudry, Alexandre; Ott, Frédéric; Alba-Simionesco, Christiane; Gougeon, Régis D.; Alcantara, Valentin; Mannes, David; Kaestner, Anders; Lehmann, Eberhard; Bellat, Jean-Pierre (Journal of Food Engineering, 2015)
Cork is the natural material stripped from the outer bark of cork oak. It is still the most used stopper to seal wine bottles and to preserve wine during storage. Cork stoppers are sorted in different classes according to apparent defects, named lenticels, which can be related to the cork macroporosity. The more lenticels there are, the worst cork quality is. The present work aims at investigating defects analysis of cork stoppers from two classes by comparing digital photography and neutron imaging. Surface analysis of defects obtained from photography leads to more surface defects in class 4 (6.7%) than in class 0 (4.1%). Neutron radiography and tomography are powerful methods that really show the defects inside the material. From neutron radiography and tomography, class 0 contains 5.4% of volume defects and class 4 6.5%. Moreover, tomography also allows observing defects distribution along the whole stopper and possible interconnectivity.
Keywords: Cork; defect detection; image analysis; neutron imaging; Porosity; tomography

NATURAL VARIABILITY OF SURFACE POROSITY OF WINE CORK STOPPERS - Oliveira, Vanda; Knapic, Sofia; Pereira, Helena (Journal international des sciences de la vigne et du vin, 2012)
Aim : The aim of this study was to characterize the variability and to quantify the surface porosity of wine cork stoppers of different quality classes. Methods and results: The porosity of 300 cork stoppers was characterized by image analysis on the lateral surface and tops. Porosity coefficient was 2.4%, 4.0% and 5.5% for premium, good and standard stoppers, respectively. The lateral surface of stoppers was heterogeneous with respect to porosity features: the tangential regions presented higher porosity while the radial regions had larger pores. Conclusion : The quality classes of cork stoppers can be differentiated by the mean values of the main porosity features of their surface. There is a natural heterogeneity of the porosity features over the external surface of cork stoppers that can be traced back to the biological basis of cork formation and the production process. Significance and impact of the study: Natural cork stoppers are the premium product of the cork industry, with worldwide recognition of quality and performance as wine sealant. Due to the large sampling and detailed observation, the results presented in this study may be used for reinforcing quality requirements, e.g., with definition of standards to improve the classification system. A better understanding of cork intrinsic variability and of the anisotropy of porosity features shown by cork stoppers is important for performance development.
Keywords: image analysis; lateral surface; natural cork stoppers; Porosity; quality classes

NATURAL VARIABILITY OF SURFACE POROSITY OF WINE CORK STOPPERS - Oliveira, Vanda; Knapic, Sofia; Pereira, Helena (Journal international des sciences de la vigne et du vin, 2012)
Aim : The aim of this study was to characterize the variability and to quantify the surface porosity of wine cork stoppers of different quality classes. Methods and results: The porosity of 300 cork stoppers was characterized by image analysis on the lateral surface and tops. Porosity coefficient was 2.4%, 4.0% and 5.5% for premium, good and standard stoppers, respectively. The lateral surface of stoppers was heterogeneous with respect to porosity features: the tangential regions presented higher porosity while the radial regions had larger pores. Conclusion : The quality classes of cork stoppers can be differentiated by the mean values of the main porosity features of their surface. There is a natural heterogeneity of the porosity features over the external surface of cork stoppers that can be traced back to the biological basis of cork formation and the production process. Significance and impact of the study: Natural cork stoppers are the premium product of the cork industry, with worldwide recognition of quality and performance as wine sealant. Due to the large sampling and detailed observation, the results presented in this study may be used for reinforcing quality requirements, e.g., with definition of standards to improve the classification system. A better understanding of cork intrinsic variability and of the anisotropy of porosity features shown by cork stoppers is important for performance development.
Keywords: image analysis; lateral surface; natural cork stoppers; Porosity; quality classes

Color-texture analysis by mutual information for multispectral image classification - El Maia, H.; Hammouch, A.; Aboutajdine, D. (2009)
In this paper, we propose a new approach for the construction of a hybrid color-texture space by using mutual information. Feature extraction is done by the co-occurrence matrix with SVM (support vectors machine) as a classifier. We apply our approach to the VisTex database and to the classification of a SPOT HRV (XS) image representing two forest areas in the region of Rabat in Morocco. We compare the result of classification obtained in this hybrid space with the one in the RGB color space.
The following values have no corresponding Zotero field: secondary-title: Communications, Computers and Signal Processing, 2009. PacRim 2009. IEEE Pacific Rim Conference on periodical: Communications, Computers and Signal Processing, 2009. PacRim 2009. IEEE Pacific Rim Conference on pages: 359-364 isbn: VO - electronic-resource-num: 10.1109/PACRIM.2009.5291344
Keywords: co-occurrence matrix; feature extraction; forest areas; hybrid color texture space; image analysis; image classification; Image color analysis; image colour analysis; Image databases; image texture; Information analysis; Morocco; multispectral image classification; Multispectral imaging; mutual information; Rabat; RGB color space; Spatial databases; SPOT HRV (XS); Support vector machine classification; support vector machines; support vectors machine (citation); VisTex database

Color-texture analysis by mutual information for multispectral image classification - El Maia, H; Hammouch, A; Aboutajdine, D (Communications, Computers and Signal Processing, 2009. PacRim 2009. IEEE Pacific Rim Conference on, 2009)
In this paper, we propose a new approach for the construction of a hybrid color-texture space by using mutual information. Feature extraction is done by the co-occurrence matrix with SVM (support vectors machine) as a classifier. We apply our approach to the VisTex database and to the classification of a SPOT HRV (XS) image representing two forest areas in the region of Rabat in Morocco. We compare the result of classification obtained in this hybrid space with the one in the RGB color space.
Keywords: co-occurrence matrix; feature extraction; forest areas; hybrid color texture space; image analysis; image classification; Image color analysis; image colour analysis; Image databases; image texture; Information analysis; Morocco; multispectral image classification; Multispectral imaging; mutual information; Rabat; RGB color space; Spatial databases; SPOT HRV (XS); Support vector machine classification; support vector machines; support vectors machine (citation); VisTex database

Influence of vision systems, black and white, colored and visual digitalization, in natural cork stopper quality estimation - Costa, Augusta; Pereira, Helena (Journal of the Science of Food and Agriculture, 2007)
Quality classification of wine natural cork stoppers is related to presence of discontinuities in the cork tissue. Automated image analysis of stoppers based on black and white cameras is used industrially for commercial classification but recently color has been introduced in image processing. This paper compares the performance of three image vision systems regarding classification accuracy of cork stoppers of good, medium and inferior quality: black and white, three-band RGB color and manual detection by digitalization in color image. A canonical discriminant analysis approach was used to compare the discriminating power between cork stopper quality in each vision system. Good discriminant results were obtained with the area of pores expressed either in total or as ratio, mean or maximum value. The use of color slightly enlarges the range of cork inspection systems and automated systems have a similar accuracy of classification to visual inspection. Copyright © 2007 Society of Chemical Industry
Keywords: canonical discriminant analysis; cork pores; image analysis; natural cork stopper; quality classification

Influence of vision systems, black and white, colored and visual digitalization, in natural cork stopper quality estimation - Costa, Augusta; Pereira, Helena (Journal of the Science of Food and Agriculture, 2007)
Quality classification of wine natural cork stoppers is related to presence of discontinuities in the cork tissue. Automated image analysis of stoppers based on black and white cameras is used industrially for commercial classification but recently color has been introduced in image processing. This paper compares the performance of three image vision systems regarding classification accuracy of cork stoppers of good, medium and inferior quality: black and white, three-band RGB color and manual detection by digitalization in color image. A canonical discriminant analysis approach was used to compare the discriminating power between cork stopper quality in each vision system. Good discriminant results were obtained with the area of pores expressed either in total or as ratio, mean or maximum value. The use of color slightly enlarges the range of cork inspection systems and automated systems have a similar accuracy of classification to visual inspection. Copyright © 2007 Society of Chemical Industry
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: canonical discriminant analysis; cork pores; image analysis; natural cork stopper; quality classification

APLICACION DEL ANALISIS DE IMAGENES AL ESTUDIO DE PARÁMETROS MORFOMETRICOS DEL CORCHO - Campos, M; Molinas, M (Scientia gerundensis, 1999)
In this work we propose a method to study cork quality from little samples throug the analy- sis of images. This method has aplications in all studies that need cork quality determination. The digital analysis of images is an apropiate option due to makes morphometry automati- cally and it allows a quick manipulation of the results. It is a fast and objective method because allows the comparative study between a high number of samples; so it could be pos- sible to compare populations or individual in order to study the influence of some ambiental or getnetic factors and have another aproach to three's selection. Here we describe an digital analysis program based on IMAGE 1.41 VDMi software for Macintosh developed to measu- re severa1 cork morphometric parameters.
Keywords: Cork quality; image analysis; methodology; morphometry; Quercus suber

APLICACION DEL ANALISIS DE IMAGENES AL ESTUDIO DE PARÁMETROS MORFOMETRICOS DEL CORCHO - Campos, M.; Molinas, M. (Scientia gerundensis, 1999)
In this work we propose a method to study cork quality from little samples throug the analy- sis of images. This method has aplications in all studies that need cork quality determination. The digital analysis of images is an apropiate option due to makes morphometry automati- cally and it allows a quick manipulation of the results. It is a fast and objective method because allows the comparative study between a high number of samples; so it could be pos- sible to compare populations or individual in order to study the influence of some ambiental or getnetic factors and have another aproach to three's selection. Here we describe an digital analysis program based on IMAGE 1.41 VDMi software for Macintosh developed to measu- re severa1 cork morphometric parameters.
Keywords: Cork quality; image analysis; methodology; morphometry; Quercus suber

Variaçáo da porosidade da cortiça ao longo do tronco dosobreiro - Lopes, Fernando; Pereira, Helena (II Congreso Forestal Español, 1997)
The within tree variation of cork quality has practical relevance when considering the methodology for estimating the quality of production using a field sampling. Samples are usually taken at breast height and an indication how quality at this level might relate to the overall average quality would help to improve estimates for the overall stand cork quality. The porosity of cork was analysed for whole stems. A total of 12 trees were evaluated, from six sites (Mora, Palma, Porto Alto, Grandola, Azaruja and Chamusca). The porosity was measured using image analysis techniques in tangential sections and in transverse sections. The cork for the different trees observed had different average porosities, ranging from 2.7% to 14.5% in the transverse section at b.h .. Within tree variatíon of cork porosity was found, with a average pattern of decreasing porosity within tree height. However a umque pattern of variation could not be established.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Cork; cork-oak; image analysis; Porosity; stem

Variaçáo da porosidade da cortiça ao longo do tronco dosobreiro - Lopes, Fernando; Pereira, Helena (II Congreso Forestal Español, 1997)
The within tree variation of cork quality has practical relevance when considering the methodology for estimating the quality of production using a field sampling. Samples are usually taken at breast height and an indication how quality at this level might relate to the overall average quality would help to improve estimates for the overall stand cork quality. The porosity of cork was analysed for whole stems. A total of 12 trees were evaluated, from six sites (Mora, Palma, Porto Alto, Grandola, Azaruja and Chamusca). The porosity was measured using image analysis techniques in tangential sections and in transverse sections. The cork for the different trees observed had different average porosities, ranging from 2.7% to 14.5% in the transverse section at b.h .. Within tree variatíon of cork porosity was found, with a average pattern of decreasing porosity within tree height. However a umque pattern of variation could not be established.
Keywords: Cork; cork-oak; image analysis; Porosity; stem

APLICACION DEL ANALISIS DIGITAL DE IMAGENES AL ESTUDIO DE LA CALIDAD DEL CORCHO - Molinas, M; Campos, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Digital Image Processing and Analysis (lA) es a computerized technique that permits to measure defined regions of interest of an image. For Al, digital images of the specimens are examined with appropiate software programs. In the present study an lA program for the quuantitative anatomy of cork has been developed. For this purpose IMAGE 1.41 VDM software for Macinstosh and Statview statistic software have been selected. Specimens from different cork populatins have been compared. The following cork parmeters: thickness, cork-rings and prososity have been measured in transverse and tangential sections. The results are analysed comparatively on each population and between populations.
Keywords: Cork quality; image analysis; morphometry; Quantitative anatomy; Quercus suber L.